1985
DOI: 10.1042/bj2320087
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of inhibitory action of TMB-8 [8-(NN-diethylamino)octyl-3,4,5-trimethoxybenzoate] on aldosterone secretion in adrenal glomerulosa cells

Abstract: The mechanism of 8-(NN-diethylamino)octyl-3,4,5-trimethoxybenzoate (TMB-8) action was evaluated in isolated adrenal glomerulosa cells. TMB-8 inhibits both angiotensin II- and K+-stimulated aldosterone secretion in a dose-dependent manner. The ID50 for angiotensin II- and K+-stimulated aldosterone secretion is 46 and 28 microM, respectively. In spite of the fact that 100 microM-TMB-8 inhibits angiotensin II-stimulated aldosterone secretion almost completely, TMB-8 (100 microM) does not inhibit angiotensin II-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1986
1986
1997
1997

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…However, it should be noted that TMB-8 may also act on protein kinase C and plasma membrane Ca 21 influx (23). In this experiment, TMB-8 also inhibited both the elevation of [Ca 2+]; and the decrease in intercellular communication induced by ionomycin.…”
Section: Effects Of Ionomycin On [mentioning
confidence: 61%
“…However, it should be noted that TMB-8 may also act on protein kinase C and plasma membrane Ca 21 influx (23). In this experiment, TMB-8 also inhibited both the elevation of [Ca 2+]; and the decrease in intercellular communication induced by ionomycin.…”
Section: Effects Of Ionomycin On [mentioning
confidence: 61%
“…This enzyme is calcium dependent. It has since been demonstrated that TMB-8 (100 ~tM) inhibits protein kinase C in isolated adrenal glomerulosa cells, but does not inhibit mobilisation of calcium from an intracellular pool [15]. It has also been suggested that TMB-8 may act by antagonising some of the actions of intracellular calcium rather than its release; for example, calcium-dependent mechanisms associated with the activation of phospholipases [16,17] and the responses of rat isolated atria to conditions of simulated ischaemia which almost certainly involve intracellular calcium ions [18].…”
Section: Discussionmentioning
confidence: 99%
“…Continuity of the diacylglycerol pathway requires mobilization of Ca 2+ to the locale of protein kinase C; translocation of this enzyme from the cytoplasm to the plasma membrane requires 2-5 x 10 -7 M Ca 2+ (Wolf et al, 1985) and its activation requires (besides diacylglycerol) >10 -6 Ca 2+ (Kishimoto et al, 1980), concentrations higher than that normally in the cytosol (Baker, 1976). Since TMB-8 blocks Ca 2+ mobilization to cytosoi (Mix et al,, 1984;Sawamura, 1985; but see also Kojima et al, 1985), we are immediately drawn to protein kinase C as a possible site where such a blockade might critically in- terfere with the pathway. Alternatively or additionally, the blockade may occur further down the pathway at a critical Ca2+-dependent step closer to the channel or at the channel itself, as proposed and discussed in more detail elsewhere (Yada et al, 1985).…”
Section: Mechanisms Of Action Of Tmb-8mentioning
confidence: 98%
“…That inhibition requires relatively high TMB-8 concentrations. A 50% inhibition, in the presence of 12.5 /~g/ml phospholipid (and 150 /~M Ca2+), requires between 100 to 250 p~M TMB-8 in one in vitro system (Kojima et al, 1985) and 300 ~M in another (Sawamura, 1985;Y. Nishizuka, personal communication), and in the presence of higher lipid concentrations (160/~g/ml) even 400/~M TMB-8 produced only a <10% inhibition (Sawamura, 1985).…”
Section: Mechanisms Of Action Of Tmb-8mentioning
confidence: 99%
See 1 more Smart Citation